Correlation of Dermatophagoides Pteronyssinus with Serum Der-P Spesific Ige and Igg4 - Nuraeni, Hanny Siti; Wibowo, Heri; Kwarta, Cytyta Putri; Rengganis, Iris (Poltekkes Kemenkes Jakarta III, 2025)
Repeated exposure to allergens induces an increase in regulatory T cells that produce interleukin 10 (IL-10) that can lead to B cells switching to immunoglobulin G4 (IgG4). Allergen-specific IgE was used as marker of allergen exposure but was only detected in atopic subjects, not in normal subjects. Therefore, an immunological marker that could be used to scan for exposure is needed. This study was conducted to determine Dermatophagoides pteronyssinus (Der p) density, serum IgE and IgG4-specific Der p levels, and to determine the correlation of Der p density with specific serum levels of IgE and IgG4 Der p in normal and atopic subjects. We calculated the amount and density of Der p in house dust mites (HDM) using the Fain and Hart (1986) method and measured Der p serum levels of IgE and IgG4 using indirect ELISA. We found that the most dominant HDM species was Der p. IgE-specific Der p level in atopic asthma patients were higher than in normal patients (p=0.002), whereas IgG4-specific Der p level in both atopic asthma and normal patients did not exhibit significant differences (p= 0.667). The density of Der p demonstrated a positive correlation with IgG4-specific Der p levels (Spearman r=0.388, p=0.008) compared to IgE-specific Der p.Compared to IgE, the density of Der p demonstrated a correlation with Der p-specific serum IgG4 levels, which means that Der p-specific IgG4 can be used to determine the exposure and accumulation of Der p in the residence of subjects.